Analisis Peranan Digital Marketing Terhadap Minat Berwirausaha (Survey Tempat Kuliner Di Kota Cimahi Kelurahan Cimahi Kecamatan Cimahi Tengah) - Devi Intan Setyaningsih; Hadi Ahmad Sukardi (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2020)
Marketing director of digital case is about the marketing including wonderful indonesia a branding the use of various based media the web as blog , a web site institute , e-mail, adwords , on the great commission nor the social networking .The lack of interest in made by is the wish of , of interest it was , as well as the willingness of work hard or are strong willed of actually trying to meet the needs of his life and create new businesses without fear with the ever present risk that was going to happen as well as will not cease to learn from the failure of a made by